2020
DOI: 10.1128/jb.00205-20
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Heme Transporter from the Energy Coupling Factor Family Is Vital for Group A Streptococcus Colonization and Infections

Abstract: Group A streptococcus (GAS) produces millions of infections worldwide, including mild mucosal infections, postinfection sequelae, and life-threatening invasive diseases. During infection, GAS readily acquires nutritional iron from host heme and hemoproteins. Here, we identified a new heme importer, named SiaFGH, and investigated its role in GAS pathophysiology. The SiaFGH proteins belong to a group of transporters with an unknown ligand from the recently described family of energy coupling factors (ECFs). A si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Moreover, it lays the foundations to further explore the influence of membrane deformations on the transport cycle in ECF transporter complexes within a near native environment. ECF transporter complexes have recently gained renewed attention with the identification of a novel haem transporter belonging to the family of ECF-type ABC transporters (34)(35)(36). As various ECF transporters complexes are encoded in the genome of various human pathogens but not in humans (37,38), it makes them attractive targets for newly designed antimicrobial compounds, for which this work represents a stepping stone towards studying their means of action on a structural level.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it lays the foundations to further explore the influence of membrane deformations on the transport cycle in ECF transporter complexes within a near native environment. ECF transporter complexes have recently gained renewed attention with the identification of a novel haem transporter belonging to the family of ECF-type ABC transporters (34)(35)(36). As various ECF transporters complexes are encoded in the genome of various human pathogens but not in humans (37,38), it makes them attractive targets for newly designed antimicrobial compounds, for which this work represents a stepping stone towards studying their means of action on a structural level.…”
Section: Discussionmentioning
confidence: 99%
“…We also characterized a mutant lacking the common components of an ECF transport system. As far as we are aware, this is only the second such system to have been identified as important for virulence, with the first being an apparent heme transporter in S. pyogenes (Chatterjee et al, 2020). This is also the first ECF system shown to be important for IE virulence in any bacterium.…”
Section: Discussionmentioning
confidence: 90%
“…Several investigations have found that genes encoding heme uptake systems are upregulated in vivo ( Cook et al., 2019 ; Rivera-Chávez and Mekalanos, 2019 ) and required for colonization and virulence of many bacterial pathogens ( Skaar et al., 2004 ; Si et al., 2017 ; Abdelhamed et al., 2018 ; Cook et al., 2019 ; Rivera-Chávez and Mekalanos, 2019 ; Chatterjee et al., 2020 ). In many cases, bacteria explore multiple host iron sources, employing both heme and siderophore-based iron acquisition systems ( Contreras et al., 2014 ; Huang and Wilks, 2017 ).…”
Section: Discussionmentioning
confidence: 99%